An Investigation into the Coordination Chemistry of Boratriazine-Based Terpy-Type Ligands - Savard, Jamie (Université d'Ottawa / University of Ottawa, 2019)
The rational design of ligand architectures that enables the development of well-defined metallic constructs has long been recognized as an avenue toward controlling and/or tuning the properties of the corresponding material. To date, one of the most widely studied ligand systems is 2,2’;6’,2”-terpyridine, whose tridentate chelating environment allows for coordination to a variety of metal ions with a wide range of geometries. The development of a terpy-like framework which incorporates a boratriazine moiety into the central ring has been recently reported by the Brusso group, namely 2,2-difluoro-4,6-bis(2-pyridyl)-1,3-dihydro-1,3,5,2-triazaborinine (Py2F2BTA) and 2,2-difluoro-4,6-bis(2-4,6-pyrimidinyl)-1,3-dihydro-1,3,5,2-triazaborinine (Pm2F2BTA). These compounds constitute unfused analogues to the extensively studied boron dipyrromethene (bodipy) family of luminophores, which are known for their high thermal resistance, chemical robustness, low photodegradation, and interesting photophysical signatures. While numerous bodipy derivatives have been studied, metal coordination with these compounds remains an intricate property to explore. Thus, the work presented herein represents the first investigations into the coordination chemistry of these novel ligand frameworks. Chapter one serves as an introduction to coordination chemistry, exploring important concepts as they relate to the field; the origin of our boratriazine based ligands is also explored within this chapter. Chapter two aims to describe trends in coordination and reactivity of these ligands with iron and cobalt metal sources of different oxidation states. The third and fourth chapter focuses on the targeted use of azide and thiocyanate ligands, respectively, to promote interesting magnetic interactions in related complexes. In the fifth chapter, luminescent metal complexes synthesized through the use of d10 metals are described. Conclusions and future outlooks are then presented in the final section, chapter six.
Keywords: Coordination Chemistry; Luminescence; Magnetism